Transformation of the media with specific reference to senior staffing at the Independent Newspapers Cape (The Cape Argus and The Cape Times) and Media24 (Die Burger) - Du Plessis, C. R (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2000.